2012
DOI: 10.1152/ajpendo.00389.2011
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and plasma membrane-initiated pathways involved in the [Ca2+]ielevations induced by iodothyronines (T3 and T2) in pituitary GH3cells

Abstract: ]i increases induced by T2 and T3. In the presence of extracellular calcium (1.2 mM), under carbonyl cyanide 4-(trifluoromethoxy)phenylhydrazone, T2 and T3 increased both [Ca 2ϩ ]i and intracellular Na ϩ concentration; nimodipine reduced the [Ca 2ϩ ]i increases elicited by T2 and T3, but inhibition of NO synthase and blockade of the Na ϩ /H ϩ pump by 5-(N-ethyl-N-isopropyl)amiloride prevented only that elicited by T3; and CB-DMB, bisindolylmaleimide, and LY-294002 (inhibitors of the Na ϩ /Ca 2ϩ exchanger, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…The reduction in the expression levels of lactoylglutathione lyase and aldehyde dehydrogenase, on the other hand, indicates a lower content of detoxifying enzymes in the liver of Ldlr −/− mice treated with either T2 or T3. Of note, consistent with what was previously reported (Silvestri et al, 2006), we observed an iodothyronine-induced decrease of the hepatic level of regucalcin, suggesting a role of calcium availability in the cellular effects of T2 and T3 (Del Viscovo et al, 2012). …”
Section: Discussionsupporting
confidence: 93%
“…The reduction in the expression levels of lactoylglutathione lyase and aldehyde dehydrogenase, on the other hand, indicates a lower content of detoxifying enzymes in the liver of Ldlr −/− mice treated with either T2 or T3. Of note, consistent with what was previously reported (Silvestri et al, 2006), we observed an iodothyronine-induced decrease of the hepatic level of regucalcin, suggesting a role of calcium availability in the cellular effects of T2 and T3 (Del Viscovo et al, 2012). …”
Section: Discussionsupporting
confidence: 93%
“…A hypothesis was derived for the mechanism of the transport of thyroid hormones from the bloodstream to the brain involving thyroid hormone transporter synthesized in choroid plexus and secreted into the cerebrospinal fluid [49]. While several mechanisms of action of T2 can be proposed, including above-discussed effects of this hormone on monoamine and integrin receptors, PI3 K-Akt signaling and TRH, given accumulated evidences concerning eminent effects of T2 on the mitochondrial respiratory chain [20, 21], biogenesis [17], and calcium and NO signalling [22], they are likely to be due to the enhancement of mitochondrial functions, a validated target of antidepressant therapy [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Unlike T3, T2 enhances mitochondrial respiration by a nuclear-independent mechanism and neither does act via thyroid hormone receptor beta, nor via AMP-activated protein kinase. T2 was demonstrated to activate reactions involved in substrate oxidation, affecting both cytochrome c reducers and cytochrome c oxidizers [20, 21], and besides it effects on respiratory chain, it was suggested to increase the downstream mechanisms that are involved in mitochondrial biogenesis [17]; these and other effects of T2 on mitochondrial pathways were shown to be distinct from the effects of T3 [22]. In contrast to the lasting l effects of T3 on metabolic rate and mitochondrial respiration, with onset delayed for 48 h, the action of T2 appears within the first few hours and does not persist for longer than 48 h and is not sensitive to actinomycin D [5, 20, 22].…”
Section: Introductionmentioning
confidence: 99%
“…After the incubation with A1254, A1254+ pyruvic acid, and pyruvic acid alone, cells were loaded with 10 μM 4,5-diaminofluorescein-2-diacetate (DAF-2DA) in a humidified 5% CO 2 atmosphere at 37°C for 30 min [ 20 ]. For control experiments, cells were incubated only in normal Krebs solution.…”
Section: Methodsmentioning
confidence: 99%